THE EFFECT OF TOLL ROAD OPERATION ON NATIONAL ROAD PERFORMANCE IN CENTRAL JAVA PROVINCE - Tri Hermani, Wahyunigsih; Setyawan, Ary; Syafi'i (Journal of Applied Engineering Science, 2023)
One of the major infrastructure development programs of the Indonesian government is the construction of toll roads, such as the Trans-Central Java toll road. The construction of these toll roads subsequently affects various aspects of the country, including the capacity and performance of the national road network. However, the government needs to analyze the effect of the toll road network on the performance of the national road network both in the existing and the coming years. Therefore, this study aims to determine the effect of the Trans Java toll road network on the performance of national roads. The study area used was the Central Java Province with a specific focus on toll roads and national roads. The analysis was processed on the EMME/3 software to form a road network with Gravity Model. The findings showed that the largest movement between 2022 and 2048 is in internal zones. It was also discovered that the Volume-Capacity Ratio value of the road network in 2022 was stable while 512 roads were projected to be unstable in 2048. Moreover, the average travel speed on national road sections in 2022 with toll roads was found to be stable up to 2030 but the speeds started reducing from 2035 to 2048 where the value was recorded to be less than 40 km/hour.